2001
DOI: 10.1080/01443610120085528
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and neonatal seroprevalence of hepatitis B surface antigen (HBsAg) in Benin City, Nigeria

Abstract: The seroprevalence of maternal and neonatal hepatitis B surface antigen (HBsAg) was determined prospectively through unlinked anonymous testing of volunteers at delivery at the University of Benin Teaching Hospital, Benin City, Nigeria. Six hundred and forty (320 mother-cord blood pairs) samples were assayed for HBsAg using hepatitis B latex test kit (Biotech Laboratory Ltd, UK). Repeatedly reactive samples were confirmed by the use of ELISA kit (Wellcome Laboratory, UK). None of these women had had a blood tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
13
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 14 publications
2
13
1
Order By: Relevance
“…The vertical transmission rate from this study was 51.6%. The vertical route is a major mode of transmission of the virus [6,7,25]. In a study done in Benin City, Nigeria, it was shown that the vertical transmission rate was 42.9% for HBsAg, which was a very high rate of transmission, similar to the rate from this study [25].…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…The vertical transmission rate from this study was 51.6%. The vertical route is a major mode of transmission of the virus [6,7,25]. In a study done in Benin City, Nigeria, it was shown that the vertical transmission rate was 42.9% for HBsAg, which was a very high rate of transmission, similar to the rate from this study [25].…”
Section: Discussionsupporting
confidence: 81%
“…This prevalence is identical to the study at the Ahmadu Bello University Teaching Hospital Zaria (ABUTH), Nigeria - 8.3% [24]. It is however, higher than the prevalence of 2.2% from a study in Benin-city, Nigeria [25]. It is also higher than the reported prevalences of 4.3% in Port-Harcourt [26], 4.4% in Lagos [10] and 4.6% in Enugu [27], all in Nigeria.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Detection of HBsAg in an individual indicates that the person is infectious. [58] The seroprevalence rate in this study is higher than the 2.1% obtained among women at the point of delivery at the University of Benin Teaching Hospital, Benin City, Nigeria,[25] and the 1.9% obtained among pregnant women in Bali, Indonesia. [26] By contrast, this prevalence rate is slightly lower than the 4.3% and 9.3% prevalence rates reported among pregnant women in Port Harcourt, Rivers State,[14] and Anambra State, South-Eastern Nigeria, respectively.…”
Section: Discussionmentioning
confidence: 71%
“…[28] The seroprevalence rate in this study is higher than the 1.6% seroprevalence rate reported among women of reproductive age in Rome, Italy[29] and the 1.9% found among pregnant women in Bali, Indonesia[30] or the 2.1% found among women at delivery at the University of Benin Teaching Hospital, Benin City, Nigeria. [31]…”
Section: Discussionmentioning
confidence: 99%